2018
DOI: 10.1002/cctc.201801684
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active and Stable Pd−GaOx/Al2O3 Catalysts Derived from Intermetallic Pd5Ga3 Nanocrystals for Methane Combustion

Abstract: Catalytic combustion of methane is widely used in industrial and transportation activities. The commonly used Pd‐based catalysts, however, are easily deactivated under hydrothermal conditions. In this work, we adopted a novel strategy to prepare a GaOx‐doped Pd/Al2O3 catalyst via the oxidative transformation of intermetallic Pd5Ga3 nanocrystals supported on γ‐Al2O3. We observed a synergistic effect between palladium and gallium oxide via formation of a bi‐functional active Pd−O−Ga phase, resulting in a highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…As shown in Figure 17, Co3.5Pd/3DOM CeO2 showed the highest activity (T90% = 480 o C at a SV of 40,000 mL/(g h) and excellent stability in the range 400−800 o C. We concluded that the excellent catalytic performance of Co3.5Pd/3DOM CeO2 was associated with its good ability to adsorb oxygen and methane as well as the unique core-shell structure of CoPd NPs. In another work, we adopted a novel strategy (i.e., the oxidative transformation of intermetallic Pd5Ga3 nanocrystals supported on Al2O3) to generate the GaOx-doped Pd/Al2O3 catalysts [46]. There was a synergistic effect between palladium and gallium oxide via formation of a bi-functional active Pd−O−Ga phase, resulting in a highly active and exceptionally stable catalyst that could markedly suppress the sintering of noble metals under harsh conditions (hydrothermal treatment at 750 o C).…”
Section: Supported Noble Metal−transition Metal Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 17, Co3.5Pd/3DOM CeO2 showed the highest activity (T90% = 480 o C at a SV of 40,000 mL/(g h) and excellent stability in the range 400−800 o C. We concluded that the excellent catalytic performance of Co3.5Pd/3DOM CeO2 was associated with its good ability to adsorb oxygen and methane as well as the unique core-shell structure of CoPd NPs. In another work, we adopted a novel strategy (i.e., the oxidative transformation of intermetallic Pd5Ga3 nanocrystals supported on Al2O3) to generate the GaOx-doped Pd/Al2O3 catalysts [46]. There was a synergistic effect between palladium and gallium oxide via formation of a bi-functional active Pd−O−Ga phase, resulting in a highly active and exceptionally stable catalyst that could markedly suppress the sintering of noble metals under harsh conditions (hydrothermal treatment at 750 o C).…”
Section: Supported Noble Metal−transition Metal Catalystsmentioning
confidence: 99%
“…Bimetallic catalysts have applications in many fields, such as electrocatalysis, photocatalysis, and even sensors. This article mainly reviews their applications in the oxidation of VOCs and 1.41Pd5.1Pt/meso-Mn2O3 2.5 vol% CH4 20,000 425 6.39 b /400 [14] PdPt@SiO2 4000 ppm CH4 133,800 420 2.353 b /420 [15] Au3Pd7/TiO2 1000 ppm CO 48,000 129 (T50%) 0.364 b /200 [16] 1.93AuPd1.95/3DOM CoCr2O4 2.5 vol% CH4 20,000 394 1.15 b /320 [17] 1.91AuPd1.80/3DOM LaMnAl11O19 2.5 vol% CH4 20,000 402 0.74 b /310 [18] 1.95Au1Pd2/meso-Cr2O3 1000 ppm toluene 20,000 165 0.091 b /120 [21] 0 0.264 b /187 [22] Au1Pd2/CZY 1000 ppm toluene 20,000 218 47.8 a /220 [23] Au-Pd-0.21Co/3DOM Mn2O3 2.5 vol% CH4 40,000 213 6.269 b /213 [24] 0.68Ag0.75Au1.14Pd/meso-Co3O4 1000 ppm toluene 80,000 112 0.633 b /112 [25] 1AuPd/3DOM LSMO 2.5 vol% CH4 40,000 335 3.63 b /270 [27] PtxAg1-x/HZ-S 120 ppm benzene 30,000 115 0.028 b /115 [28] 3.8AuPd1.92/3DOM Mn2O3 1000 ppm toluene 40,000 162 10.5 a /162 [32] 1.99AuPd/3DOM Co3O4 1000 ppm toluene 40,000 168 21.43 a /170 [33] 2.85AuPd1.87/3DOM CeO2 750 ppm trichloroethylene 20,000 415 11.8 a /300 [34] 2.05Au/0.70FeOx/CeO2 1400 ppm toluene 32,000 300 45.9 b /300 [35] 1.00Au/6CoO/SiO2-2 1.0 vol% CO 12,000 167 12.1 a /187 [36] 1.21Au−8.50Co-10/UVM-7 1000 ppm propane 20,000 320 − [34] AuCo-10/UVM-7 1000 ppm toluene 20,000 275 12.3 a /275 [37] 5.10Au/MnOx/Al2O3 0.5 vol% methane 30,000 580 39.6 a /580 [38] 0.93Au/11.2MnOx/3DOM SiO2 1000 ppm toluene 20,000 255 9.5 a /255 [39] 1.67Mn3O4−2.00Au/3DOM LSCO 1000 ppm toluene 20,000 230 20.5 a /230 [40] 1.00Pd@CeO2/Si−Al2O3 0.5 vol% methane 20,000 390 66.7 a /320 [41] 1.00Pd@ZrO2/Si−Al2O3 1.0 vol% methane 18,000 400 120.1 a /320 [42] 0.50Pd−Co/ Al2O3 0.4 vol% methane 50,000 520 128.7 a /430 [43] 0.20Pd/Co−Ce (6 : 1)/Al2O3 1000 ppm benzene 20,000 185 86.6 a /140 [44] 0.26Pd@CoOx/3DOM CeO2 2.5 vol% methane 40,000 480 1334.3 a /440 [45] 1.37Pd−GaOx/Al2O3 0.5 vol% methane 80,000 372 23.32 a /290 [46] 1.10Pd/Al2O3−36NiO 1.0 vol% methane 48,000 460 126.1 a /310…”
Section: Introductionmentioning
confidence: 99%
“…In the pursuit of enhancing thermal catalysts’ resistance to sintering, researchers have dedicated significant efforts, primarily focusing on restricting the movement of nanoparticles or individual atoms. This objective is typically achieved through various strategies, including the establishment of strong metal–support or oxide–oxide interactions, the application of oxide or carbon layers for encapsulation, and porous materials for encapsulation. Several studies conducted by Wang and Datye have employed high-temperature atom trapping techniques to confine platinum monomers, which exhibit high-temperature migration, to meticulously engineered cerium oxide supports. This innovative approach has been shown to impart remarkable thermal stability to the catalyst system.…”
Section: Introductionmentioning
confidence: 99%
“…The Pd 3d and Co 2p X-ray photoelectron spectroscopic (XPS) spectra of the samples are shown in Figure S7. The Pd species on Pd 1 /AlCo 2 O 4 −Al 2 O 3 are Pd 2+ and Pd ε+ (2 < ε ≤ 4), 32 indicating that the palladium is combined with the support via forming Pd−O bonds. The redox properties of the samples are studied using H 2 temperature-programmed reduction (H 2 -TPR) (Figure S8).…”
Section: ■ Introductionmentioning
confidence: 99%